Entertainment for Education. Digital Techniques and Systems 5th International Conference on E-learning and Games, Edutainment 2010, Changchun, China, August 16-18, 2010. Proceedings - Zhang, Xiaopeng; Zhong, Shaochun; Pan, Zhigeng; Wong, Kevin; Yun, Ruwei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 5th International Conference on E-learning and Games, Edutainment 2010, held in Changchun, China, in August 2010. The 60 revised full papers presented were carefully reviewed and selected from 222 submissions. The papers are organized in topical sections on E-learning tools and platforms; E-learning system for education; E-learning environments and applications: game techniques for edutainment; multimedia techniques for edutainment; and computer animation and graphics for edutainment.
E-Learning Tools and Platforms -- Effect of Multimedia Annotation System on Improving English Writing and Speaking Performance -- Smap: To Generate the Personalized Learning Paths for Different Learning Style Learners -- Computer-Supported Collaborative Conceptual Change -- Optimization Technique for Commercial Mobile MMORPG -- Design and Implementation of TCP/IP Protocol Learning Tool -- A Framework for Creating, Training, and Testing Self-Organizing Maps for Recognizing Learning Styles -- Simulating Dynamic Evolvement of Collective Learning Behaviors Based on Voronoi Diagram -- SPICEreading: A Three-in-One Share Platform in Cooperative English Reading -- The Design and Implementation of Middle School Physics Optical Simulation Experiment Platform -- Research on the Establishment of Structural E-Learning Resources -- Research on Virtual Experiment Intelligent Tutoring System Based on Multi-agent -- A Model-Driven Architecture Approach for Developing E-Learning Platform -- E-Learning System for Education -- Knowledge Preference Based Learning Community Construction and Service Support -- Developing an Online History Educational System to Present the Progression of Spatial Regions -- A Bibliometric Study of E-Learning Literature on SSCI Database -- Pedagogical Strategy Model in Adaptive Learning System Focusing on Learning Styles -- Transferring Design Knowledge: Challenges and Opportunities -- The Content Balancing Method for Item Selection in CAT -- The Formative Evaluation$1 (Bs Impact on Online Learning -- Psychological Perspectives on Social Behaviors of Chinese MMORPG Players -- Research on the Adaptive Strategy of Adaptive Learning System -- Research on an Educational Software Defect Prediction Model Based on SVM -- Webgame Based Collaborative Learning Design: A Case Study -- E-Learning Environments and Applications -- Design of a Medical Simulator Hard- and Software Architecture -- Design and Implementation of Semantic Matching Based Automatic Scoring System for C Programming Language -- An Analysis Framework of Activity Context in e-Learning Environments -- Distributed Cognition and Ecological Field of Learning in Network Games -- A Multimodal Virtual Anatomy E-Learning Tool for Medical Education -- To Construct the Architecture of Digital Learning Port for Free Normal Students and Analyze the Impact on Teacher Education -- Node Localization for Distributed Simulation Based on Logical Node Group in Simulation Grid -- Using Graph Edit Distance to Diagnose Student$1 (Bs Science Process Skill in Physics -- Intelligent Assessment in Math Education for Complete Induction Problems -- Research on the Method of Recomposing Learning Objects and Tools in Adaptive Learning Platform -- A Study of Formative Assessment Index System for Educational Technology Competence Based on AHP -- Research of Automatic Assessment System of Virtual Experiment in Middle School Biology Based on the Virtual Simulation Technology -- Resource Organization and Management of the Platform for Supporting Teacher Education Innovation Based on IPv6 -- Game Techniques for Edutainment -- A Glissade on the Learning Curve: Multi-adaptive Immersive Educational Games -- Experimental Development of Competitive Digital Educational Games on Multi-touch Screen for Young Children -- Strategy Research about Exploiting the Attention Resource of Learners in Educational Games -- Planning Serious Games: Adapting Approaches for Development -- UML Modeling for Software System of Edu-Game -- A Common Software Architecture for Educational Games -- O3D-Based Game Learning Environments for Cultural Heritage Online Education -- Simulator and Robot-Based Game for Learning Automata Theory -- Personalized, Adaptive Digital Educational Games Using Narrative Game-Based Learning Objects -- Multimedia Techniques for Edutainment -- Virtual Classrooms Supporting a Two-Way Synchronized Video and Audio Interaction -- Optimal Bi-directional Seam Carving for Content-Aware Image Resizing -- Real-Time Hand Gesture Recognition Based on Vision -- A Vertical Search Engine Based on Visual and Textual Features -- Hand Gesture Recognition in Natural State Based on Rotation Invariance and OpenCV Realization -- Robust Hand Posture Recognition Integrating Multi-cue Hand Tracking -- Spectrally-Based Single Image Relighting -- Multiple Layer Displacement Mapping with Lossless Image Compression -- Computer Animation and Graphics for Edutainment -- Research on Shadow Map Based Shadow Generation -- A Case for Web-Based Interactive 3D Game Using Motion Capture Data -- Sketch-Based Instancing of Parameterized 3D Models -- Digital Animation: Repercussions of New Media on Traditional Animation Concepts -- Towards Virtual Actors for Acting Out Stories -- Progressive 3D Model Compression Based on Surfacelet -- An Improved Artificial Potential Field Algorithm for Virtual Human Path Planning -- Research on Collision Detection Algorithm Based on Particle Swarm Optimization -- Parallel Collision Detection Algorithm Based on OBB Tree and MapReduce -- Creation of Tree Models from Freehand Sketches by Building 3D Skeleton Point Cloud.s
Keywords: Computer science; Education; Computer Science; Computers and Education